Media Convergence in the Platform of Video-on-Demand: Opportunities, Challenges, and Audience Behaviour - Shadia Imanuella Pradsmadji; Irwansyah Irwansyah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
The advancement of technology and society has led to innovations, including in the field of media. Media convergence has given birth to a novel audiovisual medium called Video-on-Demand (VOD), which combined the logics of television, film, home video, the internet, as well as technology. This conceptual research applied a literature review method to discuss the journey of the logic of watching television with a specific schedule and a particular medium to the understanding that television, after all, is just an artifact. The paper also discussed new habits that are developed due to the birth of VOD and how VOD branding worked. This research aimed to look at how the development of media convergence in the form of VOD brought new trends, especially in Indonesia. The paper concluded that many new opportunities were ready to be utilized by VOD platforms to develop their content and reach Indonesian audiences. However, it was also necessary to consider that Indonesia’s regulations still were not utterly supporting the development of VOD.